Infl uential typology in the academic performance of university students (2018)
The present work addresses a statistical report focused on characterizing the academic performance of university students, from the determination of associated variables, applying statistical techniques of Multivariate Analysis. The analyzes performed are based on data from a survey conducted in 2015, among the students of the Faculty of Exact, Physical and Natural Sciences and the Faculty of Philosophy, Humanities and Arts of the National University of San Juan. Through a Factorial Analysis of Multiple Correspondences, Cluster Analysis and Logistic Discrimination Analysis, it was possible to identify types of students and influential variables that diff erentiate the students according to their performance. The results contribute to bring tools that allow a valid diagnosis to eff ectively guide the interventions made by the educational institution.